Environmental Effects of MRE: Advancing the Industry through Broad Outreach and Engagement (Proceedings of the European Wave and Tidal Energy Conference, 2023)
Marine renewable energy (MRE) can benefit from broad outreach and engagement with a wide variety of audiences to raise awareness, address concerns about potential environmental impacts, generate public support, build a future workforce, share progress on research and development, and succeed within the larger blue economy. OES-Environmental is an international initiative of 16 countries that brings together the MRE community to increase understanding of environmental effects of MRE. OES-Environmental has focused on sharing research outcomes and knowledge to broad audiences that are best addressed with a variety of learning formats. Throughout these diverse outreach efforts, several important lessons have been learned. These include the importance of clarifying the main message for each audience and for each resource created; finding the best venue to deliver materials to different audiences; using language, complexity, and context that suits audience requirements and is age-appropriate; utilizing a variety of methods to share messages; and leveraging creative ideas to produce an assortment of engaging, accurate products. Creating materials tailored for specific groups has made outreach efforts more effective and has allowed for the information and findings from OES-Environmental to increase awareness of environmental effects of MRE by reaching new audiences.Based on OES-Environmental’s 2020 State of the Science Report – a comprehensive technical report providing the most up-to-date review of scientific information on environmental effects of MRE – and additional research to date, products have been designed to engage with different audiences, mainly: the MRE community (which includes regulators and advisors, project and device developers, consultants, and researchers); science, technology, engineering, and math (STEM) students; and the interested public. For the MRE community, a brochure that provides a high-level overview of environmental effects and a series of guidance documents which provide in-depth information to aid application of scientific evidence for consenting have been developed. In addition to these new resources, webinars, workshops, and Tethys – an online knowledge platform – have been used to share information and collaborate with the MRE community to advance the state of understanding. For STEM students, an animated MRE video series and a coloring book were created to offer a visual format to learn about environmental interactions with MRE devices and current research. For the interested public, an open-access magazine article and several podcast episodes were developed to expand general understanding of MRE. OES-Environmental also engages the public through ongoing content creation on various social media platforms.As OES-Environmental continues to synthesize current scientific knowledge around environmental effects of MRE, outreach and engagement will continue to be a focus to ensure important findings are communicated to diverse audiences. Sharing lessons learned by OES-Environmental around outreach and engagement can help other researchers and the MRE community broadly to communicate more effectively and accelerate industry progress.